2017
DOI: 10.1186/s13045-017-0527-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival in patients treated with ruxolitinib for myelofibrosis: COMFORT-I and -II pooled analyses

Abstract: BackgroundMyelofibrosis (MF) is associated with a variety of burdensome symptoms and reduced survival compared with age-/sex-matched controls. This analysis evaluated the long-term survival benefit with ruxolitinib, a Janus kinase (JAK)1/JAK2 inhibitor, in patients with intermediate-2 (int-2) or high-risk MF.MethodsThis was an exploratory analysis of 5-year data pooled from the phase 3 COMFORT-I and -II trials. In both trials, patients could cross over to ruxolitinib from the control group (COMFORT-I, placebo;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
198
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 247 publications
(205 citation statements)
references
References 14 publications
5
198
0
2
Order By: Relevance
“…The electronic search of PubMed identified 56 articles, of which 13 [27][28][29][30][31][32][33][34][35][36][37][38][39] were included in the review after an assessment of eligibility ( Fig. 1A).…”
Section: Systematic Reviewmentioning
confidence: 99%
“…The electronic search of PubMed identified 56 articles, of which 13 [27][28][29][30][31][32][33][34][35][36][37][38][39] were included in the review after an assessment of eligibility ( Fig. 1A).…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Ruxolitinib is the first‐in‐class JAK1/JAK2 inhibitor commercially available for the treatment of MF. Ruxolitinib ameliorates inflammation and proliferation, which leads to clinically relevant control of splenomegaly and symptoms in the majority of patients with MF, which may result in prolonged survival . Nonetheless, long‐term studies have demonstrated a lack of response in some patients and loss of response in the majority of patients .…”
Section: Introductionmentioning
confidence: 99%
“…Ruxolitinib ameliorates inflammation and proliferation, which leads to clinically relevant control of splenomegaly and symptoms in the majority of patients with MF, which may result in prolonged survival. [5][6][7][8] Nonetheless, long-term studies have demonstrated a lack of response in some patients and loss of response in the majority of patients. 9 Some patients may not tolerate ruxolitinib because of therapy-related anemia, thrombocytopenia, or nonhematologic adverse events, in particular, infectious complications.…”
Section: Introductionmentioning
confidence: 99%
“…These 2008 WHO‐defined early PMF have always been treated with ET therapies (ie, hydroxyurea, interferons, and anagrelide) that do not include ruxolitinib. Indeed, ruxolitinib is a JAK1/2 inhibitor that was approved for the treatment of primary and post‐Polycythemia Vera/post‐ET myelofibrosis based on the results of two registrative studies that proved its superiority in ameliorating MF‐related splenomegaly and symptoms compared with placebo or best available therapy …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, ruxolitinib is a JAK1/2 inhibitor that was approved for the treatment of primary and post-Polycythemia Vera/post-ET myelofibrosis based on the results of two registrative studies that proved its superiority in ameliorating MF-related splenomegaly and symptoms compared with placebo or best available therapy. 4,5 In the 2016 WHO criteria, the definition of early PMF was instead reserved to a subgroup of patients that were previously considered as full-fledged PMF. The distinction between early and overt PMF relies mainly on histology criteria, with increased age-adjusted bone marrow cellularity, decreased erythropoiesis, and lower fibrosis (grade 0-1) in early PMF.…”
Section: Introductionmentioning
confidence: 99%